Nontraditional Features of Heinrich Böll's War Books: Innovations of a Pacifist - W. Lee Nahrgang (Studies in 20th & 21st Century Literature, 1979)
Heinrich Böll, recipient of the Nobel Prize for literature in 1972, has treated the theme of war throughout his literary career; and in some ways his war books and stories differ considerably from those of other contemporary German writers. In fact, some authorities argue that none of his works are true war books in the traditional sense. Perhaps the most significant difference between Böll's works and the war books of most other authors is that he equates World War II with previous military conflicts, whereas they consider it uniquely evil because of the various crimes of the National Socialists. This nontraditional feature of Böll's works, like all others, emphasizes the negative nature of war in general. In Böll's view, all wars are essentially alike. Even defensive wars are totally negative at all times for all of those who become involved in them. Because they cause immense suffering for such large numbers of ordinary, innocent citizens of all participating countries, no wars can be justified. When Böll feels that it assists him in emphasizing this pacifistic message, he transcends the format of the contemporary German war book and produces works which are unique in many respects.
Keywords: Heinrich Böll; Nobel Prize for literature; war; theme; contemporary German writers; German; World War II; National Socialists; crimes